Superficial Fungal Infections in the Pediatric Dermatological Population of Northern Poland - Katarzyna Rychlik; Julia Sternicka; Monika Zabłotna; Roman J. Nowicki; Leszek Bieniaszewski; Dorota Purzycka-Bohdan (Journal of Fungi, 2025)
Superficial fungal infections (SFIs) remain a common dermatological issue in the pediatric population, with varying prevalence across regions and age groups. This study aimed to assess the epidemiology of SFIs among children and adolescents in northern Poland in the years 2019 to 2024. A retrospective analysis was conducted on 1237 patients under 18 years of age who underwent direct mycological examination and culture, due to suspicion of SFIs. Data were evaluated based on age, gender, infection site, fungal species identified, and place of residence. The prevalence of SFIs in the studied population was 21.4%. The most frequently isolated fungi were Microsporum canis and Trichophyton rubrum complex. Infection patterns varied by age: tinea capitis and tinea cutis glabrae predominated in younger children, while adolescents were more affected by tinea pedis and onychomycosis. A higher proportion of positive results was observed in rural patients, although more urban dwellers were tested. Species distribution also varied with gender and place of residence. No significant change in SFI prevalence or pathogen profile was observed over the study period. This study provides updated insights into the epidemiology of SFIs in Polish children, highlighting the influence of demographic and environmental factors. The findings underscore the importance of accurate diagnosis and suggest a need for further research into behavioral and socio-economic contributors to infection patterns.